Intensity-modulated radiotherapy combined with systemic atezolizumab and bevacizumab in treatment of hepatocellular carcinoma with extrahepatic portal vein tumor thrombus: A preliminary multicenter single-arm prospective study - Wang, Kang; Xiang, Yan-Jun; Yu, Hong-Ming; Cheng, Yu-Qiang; Liu, Zong-Han; Zhong, Jing-Ya; Feng, Shuang; Ni, Qian-Zhi; Zhu, Hong-Fei; Pan, Wei-Wei; Li, Jing-Jing; Liang, Chao; et al. (Frontiers in Immunology, 2023)
Background & Aims: The efficacy and safety of systemic atezolizumab and bevacizumab (atezo/bev) in treatment of patients with unresectable hepatocellular carcinoma (HCC) have been demonstrated. However, the efficacy of this treatment in patients with HCC and extrahepatic portal vein tumor thrombus (ePVTT) is not satisfactory. This study aimed to study the efficacy and safety of combining intensity-modulated radiotherapy (IMRT) with systemic atezo/bev in treatment of these patients. Methods: This multicenter prospective study included patients with ePVTT treated with IMRT combined with atezo/bev from March to September 2021 in three centers in China. The outcomes of this study included objective response rate (ORR), overall survival (OS), progression-free survival (PFS), time to progression (TTP), and association between response and tumor mutational burden (TMB). Treatment-related adverse events (TRAEs) were analyzed to assess safety. Results: Of 30 patients in this study, the median follow-up was 7.4 months. Based on the Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1, the ORR was 76.6%, the median OS for the entire cohort was 9.8 months, the median PFS was 8.0 months, and the median TTP was not reached. This study failed to establish a significant correlation between TMB with any of the following outcomes, including ORR, OS, PFS or TTP. The most common TRAEs at all levels were neutropenia (46.7%), and the most common grade 3/4 TRAE was hypertension (16.7%). There was no treatment-related deaths. Conclusions: IMRT combined with atezo/bev showed encouraging treatment efficacy with an acceptable safety profile, making this treatment to be a promising option for HCC patients with ePVTT. Further studies are requied to support the findings of this preliminary study.